Breaking Murphy's law : how optimists get what they want from life-- and pessimists can too - Segerstrom, Suzanne C. (Guilford Press, 2006)
Presents a survey of the scientific data on optimism (including the author's award-winning research) to reveal that it's not what you believe about the future that matters, but what you do about it. This book aims to teach readers practical ways to appropriate the habits and skills that optimists use to get what they want from life.